Peran BUMDES dalam Revitalisasi Kawasan Wisata Budaya di Kawasan Pantai Parangtritis - Muhamad Muhamad; Dicky Sopjan; Sri Rahayu Budiani; Nurul Chamidah; Endah Nurhawaeny Kardiyati (Jurnal Pemberdayaan Umat, 2022)
Purpose: The purpose of this research is to study the process of revitalizing the presence of Village-owned Enterprises (BUMDes) in village development innovations, especially in the revitalization of cultural tourism areas in the Parangtritis beach area. Research Methodology: This method of implementing community service is carried out in a qualitative descriptive manner with a Focus Group Discussion (FGD) with an approach to the concept of active involvement of BUMDes in revitalizing the cultural tourism area. All BUMDes members in the organizational structure are actively involved. Results: The presence of BUMDes is to strengthen the economy of the rural communities. BUMDes is the right of the village to take advantage of the Village Law rules which give authority to the village government to innovate in village development, especially in terms of improving the village economy and welfare for village communities. Conclusions: Community service show that there is an active role for BUMDes in revitalizing the area, especially in carrying out inventory and planning for the revitalization of cultural tourism areas. . Limitations: The limited time for the implementation of the service is very short, namely 6 months. Contribution: The research contribution contributes to the revitalization of the area which is an asset for the village.of parties directly related to the KUBE program. As a result,